Exploring the accurate size measurement method for two typical nanostructures basing on SEM imaging. (November 2019) - Zhang, Peng
Highlights: Gold nanorods and a silicon trapezoidal line were studied for aspect ratio and linewidth measurements, respectively. This work adopted an image-based method with a Monte Carlo simulation to obtain an accurate value of the aspect ratio. Bias for top-CD and bottom-CD was performed systematically for a silicon trapezoidal line under various parameters. Abstract: The accurate size measurement has been necessary in modern nanotechnology /semiconductor industry. Based on a sophisticated Monte Carlo scanning electron microscope simulation tool, gold nanorods and the silicon trapezoidal line, two commonly used nanostructures, were studied for aspect ratio and linewidth measurements, respectively. Accurate measurement for aspect ratio is significant for the optical property of gold nanorods. This work adopted an image-based method with a Monte Carlo simulation to obtain an accurate value of the aspect ratio. In the case of 10% division interval, it was found that if the distances at 40% and 50% of the height of the two peaks in a line-scan profile are respectively taken as the lengths of long axis and short axis of nanorod, the aspect ratio can be obtained with minimum error. Besides, a systematic calculation of bias for top-CD and bottom-CD was performed for a silicon trapezoidal line under various parameters. Calculation results show that the bias for bottom-CD is less than that for top-CD due to side wall angle. The bias increases with side wall angle and primary electron energy, but decreases with width of trapezoid top surface.